A Narrative Review of Multidisciplinary Rehabilitation in Juvenile Idiopathic Arthritis - Retamal-Espinoza, M; Cancino-Jimenez, J; Cifuentes-Silva, E (Springer Science and Business Media Deutschland GmbH, 2025)
Juvenile idiopathic arthritis (JIA) is a chronic condition affecting children, marked by persistent joint inflammation driven by innate and adaptive immune responses involving macrophages and T and B lymphocytes. These responses promote tissue damage and inflammation via elevated pro-inflammatory cytokines, while anti-inflammatory cytokines are also present, but without a clear linear relationship. JIA can result in long-term physical disabilities, making a multidisciplinary rehabilitation approach essential to enhance patients quality of life. This approach includes a collaborative team addressing pain reduction, joint and muscle function improvement, and patient autonomy. Key interventions involve physical therapy to maintain and enhance joint mobility and muscle strength. Evidence suggests that physical exercise may modulate immune responses and pro-inflammatory cascades, critical in JIA pathogenesis. However, further studies are required to determine the most effective exercise protocols for this population and their specific immunomodulatory benefits. A narrative literature review was conducted using PubMed (2014–2024) with the terms “juvenile idiopathic arthritis,” “rehabilitation,” and “exercise,” supplemented by references from systematic reviews and meta-analyses, and additional historical data from Google Scholar. The search yielded 52 relevant articles, primarily involving pediatric subjects under 18 years. These studies highlight the multifaceted benefits of multidisciplinary management in JIA, including improved physical and functional outcomes. Despite promising evidence, further research is warranted to refine exercise protocols tailored to JIA, ensuring optimal therapeutic impact on inflammation and disease progression. © The Author(s), under exclusive licence to International League of Associations for Rheumatology (ILAR) 2025.